2011
DOI: 10.3109/17482968.2011.584627
|View full text |Cite
|
Sign up to set email alerts
|

Talampanel reduces the level of motoneuronal calcium in transgenic mutant SOD1 mice only if applied presymptomatically

Abstract: We tested the efficacy of treatment with talampanel in a mutant SOD1 mouse model of ALS by measuring intracellular calcium levels and loss of spinal motor neurons. We intended to mimic the clinical study; hence, treatment was started when the clinical symptoms were already present. The data were compared with the results of similar treatment started at a presymptomatic stage. Transgenic and wild-type mice were treated either with talampanel or with vehicle, starting in pre-symptomatic or symptomatic stages. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Talampanel (4) is a non-competitive AMPA antagonist, reduces motor neuronal calcium levels in SOD1 mice models if applied presymptomatically and is effective only during the early stage of the disease [44]. A phase II study with telampaneltreated 60 ALS patients demonstrated decrease in ALS Functional Rating Scale (ALSFRS), muscle strength and hand movements [45].…”
Section: Excitotoxicity In Als and Therapeutic Strategiesmentioning
confidence: 98%
“…Talampanel (4) is a non-competitive AMPA antagonist, reduces motor neuronal calcium levels in SOD1 mice models if applied presymptomatically and is effective only during the early stage of the disease [44]. A phase II study with telampaneltreated 60 ALS patients demonstrated decrease in ALS Functional Rating Scale (ALSFRS), muscle strength and hand movements [45].…”
Section: Excitotoxicity In Als and Therapeutic Strategiesmentioning
confidence: 98%
“…There is evidence that excess extracellular glutamate, especially via AMPA receptors, is a key factor in ALS neuropathogenesis [78]. In vivo studies of SOD1 mice models support the beneficial effects of AMPA antagonists such as talampanel [79]. However, it was demonstrated that the neuroprotective effects of talampanel were only present when it was applied during the early stage of the disease.…”
Section: Potential Drugs Immunotherapy and Stem Cells Therapy Formentioning
confidence: 99%
“…Ceftriaxone prevents glutamate neurotoxicity, and when initiated at disease onset delays loss of muscle strength and body weight and prolongs survival [61]. Talampanel, a noncompetitive AMPA antagonist, reduces motorneuronal calcium levels if applied presymptomatically [62]. Memantine is an FDA-approved drug used for the treatment of Parkinsonism, vascular dementia, and Alzheimer’s disease.…”
Section: Protein Degradation Pathways and Sod1-clearing Agentsmentioning
confidence: 99%